Sensitivity pattern of azithrymycin, ofloxacin and ceftriaxone in ciprofloxacin resistant salmonella causing enteric fever - Kawser, Shamima; Miah, Ruhul Amin; Sabah, Khandker Md Nurus; Begum, Tanzima; Sultana, Shahin (Journal of Dhaka Medical College, 2013)
The therapeutic alternatives available for use against ciprofloxacin resistant enteric fever isolates in an endemic area are limited. A cross sectional study was carried out in the Department of Microbiology & Immunology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from January to December 2008, to see the sensitivity pattern of azithrymycin, ofloxacin and ceftriaxone in ciprofloxacin resistant salmonella causing enteric fever. In this study, the MICs of various drugs were determined for 100 enteric fever isolates (72 Salmonella enterica serovar Typhi and 28 Salmonella enterica serovar paratyphi A). By agar dilution method, 40% Salmonella strains were ciprofloxacin resistant showing MIC values of (4-8 mg/ml), 36% strains were intermediate sensitive with MIC values of 1 to 4 mg/ml and 24% strains were sensitive to ciprofloxacin showing MIC values of 0.125 to 1 mg/ml. All ciprofloxacin- resistant isolates were sensitive to ofloxacin (inhibitory zone diamater 16-32mm), ceftriaxone (inhibitory zone diameter 21mm), 66.66 % isolates were sensitive to azithromycin. These results indicate that ofloxacin and ceflriaxone may be convenient alternative antimicrobial agents for Salmonella isolates. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15627 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 55-60